Ultimum Remedium in Environmental Criminal Law Enforcement - Aprilia Dyah Puspitasari; Abdullah Tri Wahyudi; Wardah Yuspin (Jurnal Ilmu Sosial dan Humaniora, 2026)
In environmental cases, some have adopted the principle of Ultima Ratio as a last resort to address the problem. The aim is to enforce environmental law, distinct from criminal law enforcement, and to apply the Ultimum Remedium Principle of Environmental Law according to Positive Law. This study employs a normative juridical method and literature-based data collection techniques. The results of the Research are the principle of ultimum remedium (last resort) in resolving environmental criminal cases. In 2024, police case files at the investigation stage were not completed for 187 cases, and in 2025, case files in Pegcourt were not completed for 21 cases. The criminal process involves police reports, stalking investigations at the prosecutor's office, and court verdicts. Ultimum Remedium is invoked to encourage settlement through mediation. In 2024, there will be 32 cases outside the Court with agreements, and in 2025, 38 cases with contracts and negotiations. The conclusion is that the Law and Government Regulation on Environmental Management regulates environmental law enforcement through criminal law. Under government regulations, environmental damage can be subject to administrative, civil, and criminal penalties. In addition, the term Ultimum Remedium encourages mediation through agreements or negotiations.